Great expectations? Pre‐transplant quality of life expectations and distress after kidney transplantation: A prospective study. (12th December 2013) - Schulz, Torben; Niesing, Jan; Homan van der Heide, Jaap J.; Westerhuis, Ralf; Ploeg, Rutger J.; Ranchor, Adelita V.
<x xml:space="preserve">Abstract</x> Objectives Previous research suggests that prior to kidney transplantation, patients overestimate their post‐transplant quality of life (QoL). The current study aimed to corroborate these findings, identify determinants of QoL overestimation, examine its association with subsequent distress, and clarify the role of optimism. Design Prospective observational study. Methods Physical, psychological, and social QoL expectations, actual QoL, and distress (GHQ‐12) of participants (56% male) were prospectively assessed before (T0; n = 228) and 3 (T1; n = 149), 6 (T2; n = 146), and 12 (T3; n = 114) months after successful transplantation. Results Patients who were treated with haemodialysis before transplantation reported greater physical QoL overestimation than those who received treatment with peritoneal dialysis. Neither physical nor social QoL overestimation at T1 was prospectively associated with increased distress at T2 or T3. The interaction between optimism and social QoL overestimation at T1 (β = −.56, p < .001) for distress at T2 was significant, with patients low in optimism experiencing more distress after QoL overestimation. Conclusions QoL overestimation is not associated with subsequent distress. Findings suggest that patients low in optimism are more vulnerable to distress following QoL overestimation. Statement of contribution What is already known on this subject? Kidney transplantation improves patients' quality of life. Prior to kidney transplantation, patients overestimate the scale of this improvement. What does this study add? Quality of life overestimation is not associated with subsequent distress. When optimism is low, kidney transplant recipients experience higher distress following quality of life overestimation.